2011
DOI: 10.1007/s10096-011-1468-7
|View full text |Cite
|
Sign up to set email alerts
|

Serotype 3 is a common serotype causing invasive pneumococcal disease in children less than 5 years old, as identified by real-time PCR

Abstract: Serotype 3 is one of the most often detected pneumococcal serotypes in adults and it is associated with serious disease. In contrast, the isolation of serotype 3 by bacterial culture is unusual in children with invasive pneumococcal disease (IPD). The purpose of this study was to learn the serotype distribution of IPD, including culture-negative episodes, by using molecular methods in normal sterile samples. We studied all children<5 years of age with IPD admitted to two paediatric hospitals in Catalonia, Spai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…In a previous study using real-time PCR for identification, serotype 3 was reported to be a common serotype causing IPD in children in Spain (26). In the present analysis, cases caused by serotype 3 represented Ͻ8% in both periods, without a significant reduction in IR in the PCV13 period.…”
Section: Discussionsupporting
confidence: 46%
“…In a previous study using real-time PCR for identification, serotype 3 was reported to be a common serotype causing IPD in children in Spain (26). In the present analysis, cases caused by serotype 3 represented Ͻ8% in both periods, without a significant reduction in IR in the PCV13 period.…”
Section: Discussionsupporting
confidence: 46%
“…PM was defined by characteristic clinical signs and symptoms (stiff or painful neck, vomiting, headache, persistent fever, bulging fontanelles) and compatible cerebrospinal fluid (CSF) alterations (CSF cell count up to 10 cells/mm 3 ) along with isolation of S. pneumoniae and/or DNA detection of pneumococcal genes by Real-Time PCR 16 in blood or cerebrospinal fluid.…”
Section: Methodsmentioning
confidence: 99%
“…Detection of this serotype represented a 5-fold increase with respect to detection by culture. It is noteworthy that, although several published studies have reported a lower frequency of serotype 3 in children [22,23], a recent study in our geographical area discussed the fact that serotype 3 could have been underestimated in children due to difficulties in recovering it in culture [8].…”
Section: Discussionmentioning
confidence: 97%
“…The addition of molecular techniques to culture could provide a more exact picture of the nasopharyngeal pneumococcal population based on their ability to detect low density and multiple-serotype carriage. Particularly for the invasive disease population, the use of these techniques may lead to a change in the real prevalence of some serotypes, such as 1 and 3, that could have been underestimated due to their difficult recovery by culture [7,8].…”
Section: Introductionmentioning
confidence: 99%